Optimal Time-Consistent Fiscal Policy with Finite Lifetimes - Calvo, Guillermo A.; Obstfeld, Maurice (Econometrica, 1988)
This paper analyzes aspects of optimal fiscal policy for economies with capital ac cumulation and finitely-lived, heterogeneous agents. For a particular utilitarian social welfare function, the problem faced by a central planner can be broken down into two subproblems: a standard problem o f optimally allocating aggregate consumption over time and a problem of distributing aggregate consumption optimally at each moment among those alive. If it can use a sufficiently rich set of lump-sum taxes and transfers, the government can replicate the command optimum as a market equilibrium outcome. No issue of government debt is needed to achieve this decentralization. Copyright 1988 by The Econometric Society.